"This snack is too small - I'll take a different one": Quantifying 'norm' and 'choice' boundaries to inform effective portion-reduction strategies. (1st April 2022) - O Shahrokni, Roya; Ferriday, Danielle; Miguel, Sonia; Laurent, Aurelie L.; Brunstrom, Jeffrey M.
Abstract: Previous research suggests that portion sizes can be categorised as 'normal' or 'abnormal' and that reduced portions which are still categorised as normal do not promote compensatory responses in intake. However, a critical question remains – will consumers choose a reduced portion product from among standard portion competitors? For the first time, we explore the effects of portion reduction on food choice. Participants (N = 45) categorised 20 different portions (range 40–420 kcal) of five snacks as normal or abnormal (to quantify individual 'norm boundaries' for each food) and rated their desire to eat each snack. Using a 2-alternative forced choice hypothetical task, we then calculated a 'choice boundary' by offering smaller portions of their most-desired snack (range 40–240 kcal) alongside standardised portions (240 kcal) of the less-desired foods. Boundaries were derived using probit analysis (choice boundary mean = 185.8 kcal, SD = 54, norm boundary mean = 127.3 kcal, SD = 49.5) and these deviated significantly (p < .01, d = 0.98, mean difference = 58.0 kcal, SD = 59.1). Critically, this shows that only a small reduction – where the product is still considered normal - can nudge a consumer to select an alternative. Choice boundaries were also affected by differences in desire to eat; when two foods were desired to a similar degree, only minor reductions in the size of the favourite food elicited a switch in choice. Together, these findings indicate that portion reduction can also influence food choice, highlighting the importance of measuring choice boundaries before reformulating commercial products.